The Role of Training and Assistance in Improving the Utilization of Accounting Information Systems to Improve The Quality of Financial Reports In the SMEs Sector - Eddy Sarwono, Aris (International Journal of Science, Technology & Management, 2025)
This study aims to analyze the role of training and mentoring to improve the quality of financial reports in the SMEs sector in Sragen Regency by utilizing an accounting information system. This study uses a survey method with the type of data used quantitative data and primary data sources. Sampling used a purposive sampling technique and 58 SMEs became respondents in this study. The results of the study concluded that the use of Accounting Information System has a positive and significant effect on the quality of financial reports, while the understanding of accounting no effect on the quality of financial reports. Training and mentoring variables moderate the relationship between use of Accounting Information System and quality of financial reports. Meanwhile, the variable use of Accounting Information System on the quality of financial reports cannot be moderated by training and mentoring.